Penyederhanaan Izin Usaha Pasca Undang-Undang Cipta Kerja, Berdasarkan Prinsip Perizinan Berbasis Besarnya Resiko Berusaha - Rosari, Anton; Darnis, Darnis; Patra, Lerri (Dinasti Review Publisher, 2024)
Simplifying licensing is an important issue in the administration of government and public services today. This policy was implemented because in the past there were too many types of permits that were handled by the community and this could make it difficult for the community to create jobs.